(untitled) (Purbanchal University Health Journal, 2024)
Introduction: Ageing is a process of gradual change in physical appearance and mental situation that cause a person to grow old. Morbidity increases with age and enhances the burden of health problems that result in new challenges to meet additional demands. In the ageing population, health problems, and health care utilization should be assessed carefully and addressed. This study aimed to identify chronic morbidities, health problems, health care seeking behavior and health care utilization among the elderly. Objective: This study aimed to identify health services utilization among the elderly peoples. Method: A descriptive cross-sectional study was conducted among elderly people of Itahari Submetropolitian city through face-to-face interview. Data collection involved assessment of health care utilization among the elderly peoples. Multi stage sampling was done were descriptive and inferential analysis were done. Result: The study of 323 participants (mean age 71.84 ± 7.9 years) found that most were male, lived with sons, and 72.5% had an illness. Multiple mild-severity illnesses affected 34.1%, while 70.6% utilized healthcare services, with age and chronic illness significantly influencing usage. Improving elderly healthcare requires affordable services, stronger primary care, specialized geriatric programs, and better accessibility will increase more health service utilization. Conclusion: The study revealed a high burden of multiple illness among the elderly, with many utilizing health services. However, barriers such as cost, illness severity, distance, and belief in traditional healing limited access. Most participants had chronic conditions, and nearly half believed in traditional treatments. Improving awareness and accessibility of government health services is essential to enhance healthcare utilization among older adults.